Books Without Borders, Volume 2
XIV, 204 p. 5 illus.
Keywords: This volume focuses on the publisher's series as a cultural formation - a material artifact and component of cultural hierarchies. Contributors engage with archival research, cultural theory, literary and bibliometric analysis (amongst a range of other approaches) to contextualize the publisher's series in terms of its cultural and economic work.